What do women like? A quantitative study of the female behavior of sparkling wines consumers - Miriam de Oliveira Dornelles; Cláudio Farias; Shana Sabbado Flores (Wine Economics and Policy, 2022)
The purpose of this paper is to investigate the purchase process of the sparkling wines female consumers, in order to understand the variables that influence the purchase process of this product. The consumer behavior in the purchase decision process is one important topic of the marketing studies, to the extent that it helps to explain how decisions are made and what elements determine them, it can support strategic marketing decisions. The importance of gender segmentation has been highlighted in several studies; in addition, women have made most purchases and their influence in purchase decision has been highlighted. This study uses data from a survey carried out on a representative sample of 1,003 female consumers from Brazil. It was used a five levels Likert scale; Independent tests and correspondence analyses were performed. The study could identify the five main factors influencing the choice. Also, the results contribute to elucidate points such as confidence to choose and consumption occasions and contexts.
Keywords: 330; Brazil; consumer behavior; purchasing decision; gender